Molecular Detection of Antimicrobial Resistant genes with special reference to ESBL in E. coli from Diarrheic Piglets - Grakh, Kushal; Mittal, Dinesh; Prakash, Anand; Moudgil, Pallavi; Kumar, Pankaj (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Antimicrobial resistance (AMR) has been identified as a global threat. E. coli is known to carry different AMR genes and responsible forhuge economic loss owing to AMR. In the present study 14 previously confirmed E. coli isolates associated with piglet diarrhea wereanalyzed for pathogenicity and hemolysin production traits, molecular detection of AMR genes, screening for extended-spectrumβ-lactamases (ESBLs) by phenotypic and molecular methods. These isolates were previously identified as E. coli by Vitek 2 Compact systemand revealed antimicrobial resistance using the disc diffusion method. After re-confirmation using PCR amplification of uspA (universalstress protein) gene, these isolates were characterized for pathogenic traits. AMR genes for penicillins, cephalosporins, tetracyclines,and sulfonamide drugs were probed in 14 isolates. Phenotypic ESBL detection method revealed 5/14 (37.5%) of the isolates as ESBLpositive. Molecular methods using ESBL genes found 6/14 (42.8%) isolates as ESBL positive. We also investigated the presence of sulfaand tetracyclines AMR genes in these isolates. Out of 14 isolates, the sul2 gene in five isolates, sul1 gene in seven isolates and tetB genein two isolates, was detected out of 14 isolates. None of the isolates were found to carry tetA, tetM, and dfrA1 genes. The present studyfinds swine E. coli isolates carrying blaTEM, blaSHV, and blaCTX-M genes along with other antimicrobial resistance genes viz., sul1, sul2,and tetB. Thus, this study suggests further surveillance for the detection of resistance genes among E. coli isolates of swine-origin asthese genes can be transferred to human E. coli isolates
Keywords: E. coli; Antimicrobial-resistant genes; ESBL; Swine; PCR